BLOCKCHAIN TECHNOLOGY IN AGRO-INDUSTRIAL SUPPLY CHAIN: REVIEW - Ekawati, Ratna; Arkeman, Yandra; Suprihatin, Suprihatin; Sunarti, Titi Candra (JEMIS (Journal of Engineering & Management in Industrial System), 2021)
This paper provides a review of the application of blockchain technology in industrial supply chains in general. It aims to investigate how current blockchain technology is and its applications and to look for research loopholes that have not been done before. The theory of several research papers that have been published in journals to date, along with several reports from the grayish literature as a means of streamlining judgments about growing blockchain-based supply chains is included in this review. The research step is to identify papers based on the year of publication so that a theory-based understanding of blockchain technology in the Agro-Industrial Supply Chain ecosystem, between 2007 and 2019. Blockchain technology in the agro-industry supply chain described in the framework in 2018 is 6.57%, while the implication for the case study is 9.11% and identified in the hypothesis with a questionnaire regarding blockchain recognition and exploration so that 4.5% of the blockchain model simulation. Based on the graph, there are 52% of blockchain research articles on the agro-industrial supply chain will be followed up by researchers, thereby increasing the value chain in agro-industry more. Research that discusses the value (value) in the supply chain that occurs from upstream to downstream in the agro-industrial supply chain ecosystem is very little, only around 2%. Excellence blockchain can identify the stakeholders that exist in the supply chain in each ecosystem from upstream to downstream processes so that it can transform a rigid and uncertain supply chain system into an efficient performance supply chain with transparency and trust between stakeholders so that integration, collaboration, and accuracy accurate data information